Analysis of nursing records as to care quality: a retrospective descriptive exploratory study of quantitative approach. - Dagmar Willamowius Vituri; Laura Misue Matsuda (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2008)
Uneasiness in professional practice arises due to failures detected in the nursing records and, consequently, in the given assistance. This study is intended to support discussions and meditation on this issue, aiming at the promotion of quality care. The purpose is to analyze the 2003-2006 Yearly Nursing Records Quality Evaluation Reports accomplished by the nursing team of a medical surgeon unit of a school hospital. It is a retrospective descriptive exploratory study of quantitative approach. The results show that, within the standard of 80%, the items with the lowest values refer to whether there were notes on aspect and evolution of skin wounds and whether the prescribed treatment was countersigned, circulated and justified. It was concluded the service in question need invest in training of the team with regard to proper documentation of nursing care through continuous and permanent training programs as well as restore the role of the nurse as team leader, so that he can raise consciousness as to the importance and the correct and sufficient observance of the written records in the care process. (1) Matsuda, LM, Silva DMPP, Évora YDM, Coimbra JAH. Anotações/registros de enfermagem: instrumento de comunicação para a qualidade do cuidado? Rev Eletrônica Enferm 2007;8(3): 415-421. [citado jul 2 2007]. Disponível em: http://www.fen.ufg.br/revista/revista8_3/v8n3a12.htm ((16) Ochoa-Vigo K, Pace AE, Santos CB. Análise retrospectiva dos registros de enfermagem em uma unidade especializada. Rev Latinoam Enferm 2003;11(2):184-91. (17) Possari JF. Prontuário do paciente e os registros de enfermagem. São Paulo: Iátria, 2005.